2020
DOI: 10.1177/2470547020917623
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Positive Visual Stimuli Before and After Symptoms Provocation in Posttraumatic Stress Disorder – A Functional Magnetic Resonance Imaging Study of Trauma-Affected Male Refugees

Abstract: Background Symptoms of anhedonia are often central to posttraumatic stress disorder (PTSD), but it is unclear how anhedonia is affected by processes induced by reliving past traumatic memories. Methods Sixty-nine male refugees (PTSD = 38) were interviewed and scanned with functional magnetic resonance imaging while viewing positive, neutral and Scrambled Pictures after being read personalized scripts evoking an emotionally neutral memory and a traumatic memory. We further measured postprovocation state symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…The occipitotemporal network, which incorporates these pathways, specifically is implicated in the processing of emotional stimuli in typically developing youth (Kravitz et al, 2013) and may be impacted by trauma exposure and/or PTSD. One study has implicated reduced gray matter volume and thickness in the bilateral primary visual cortex as well as the middle occipital area of adults who witnessed domestic violence in childhood (Tomoda et al, 2012), while another investigation of adult refugees with PTSD showed decreased activity in primary visual cortex to positive images compared to controls (Uldall et al, 2020). Emotional attention and stimuli have also been shown to modulate V4 activity indicating that modulation of this area is likely to occur from higher-order attention areas (Bi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The occipitotemporal network, which incorporates these pathways, specifically is implicated in the processing of emotional stimuli in typically developing youth (Kravitz et al, 2013) and may be impacted by trauma exposure and/or PTSD. One study has implicated reduced gray matter volume and thickness in the bilateral primary visual cortex as well as the middle occipital area of adults who witnessed domestic violence in childhood (Tomoda et al, 2012), while another investigation of adult refugees with PTSD showed decreased activity in primary visual cortex to positive images compared to controls (Uldall et al, 2020). Emotional attention and stimuli have also been shown to modulate V4 activity indicating that modulation of this area is likely to occur from higher-order attention areas (Bi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%